USABILITY TESTING PADA BANKING CREDIT DOCUMENT MANAGEMENT SYSTEM STUDI KASUS: KC BANK XYZ. - Hidayatuloh, Rahmat; Basri, Hasan (Innotech: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2024)
The Banking Credit Document Management System is a credit document management system in which credit documents are stored electronically within the system while physical documents are stored in a centralized, standardized, and integrated location. To create a high-quality information system application, an evaluation must be performed as a means of determining a system's success. This study was carried out with the goal of evaluating the quality of usability. Usability Testing has six characteristics with variables: Learnability, Efficiency, Memorability, Errors, and Satisfaction. Usability testing requires respondents to complete a questionnaire containing questions about usability variables, which will result in conclusions and suggestions for improving and developing the system being evaluated. The number of participants was 49, and the usability quality rating was 86.83%, which was considered very good.